Muscle activities of the brachioradialis and extensor carpi radialis longus according to the type of backhand stroke in badminton - Lee, G.-H.; Lim, B.-O. (The Korean Journal of Sports Medicine, 2020)
Purpose: The purpose of this study was to investigate the muscle activities of the brachioradialis and extensor carpi radialis longus according to the type of backhand stroke in badminton. Methods: To measure the muscle activities, we used electromyography (EMG) equipment to measure EMG values by performing maximal voluntary contraction (MVC) of the forearm muscles, which depends on the type of backhand stroke. With these values, the %maximum voluntary isometric contraction values were obtained. The data were calculated using SPSS ver. 21.0 and one-way repeated measures analysis of variance with a post-hoc least significant difference test. Results: In this study, the backhand clear achieved higher maximum muscle activity values than those by the backhand push, under clear, and drive in the brachioradialis. The backhand smash achieved higher maximum muscle activity values than those by the backhand push in the extensor carpi radialis longus. Conclusion: The backhand clear is associated with a higher injury rate than those associated with the backhand push, under clear, and drive. The backhand smash is associated with a higher rate of the occurrence of tennis elbow than that associated with the backhand push. To prevent injuries, it is considered that the forearm's strength, stretching before and after exercise, and sufficient time to rest are important.